2005
DOI: 10.1038/sj.bjc.6602471
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of serum insulin-like growth factor-I (IGF-I), IGF-II, IGF-binding protein-3 and breast cancer risk

Abstract: The associations between serum concentrations of insulin-like growth factor-I (IGF-I), IGF-II and IGF-binding proteins (IGFBP)-3 and risk of breast cancer were investigated in a nested case -control study involving 117 cases (70 premenopausal and 47 postmenopausal at blood collection) and 350 matched controls within a cohort of women from the island of Guernsey, UK. Women using exogenous hormones at the time of blood collection were excluded. Premenopausal women in the top vs bottom third of serum IGF-I concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 28 publications
4
82
2
2
Order By: Relevance
“…Thus, since our study population consisted primarily of postmenopausal women, it is not surprising that we detected no relationship between IGF-I and breast cancer risk. We also did not find any association between IGF-II and risk of breast cancer, as has been reported previously (7). However, evidence from animal and cell line experiments examining the role of IGF-II in carcinogenesis indicates increased rates of malignancies, including breast tumors (28)(29)(30)(31)(32)(33), and results from one case-control study found a positive association between IGF-II and ER-positive but not ER-negative breast cancer among postmenopausal women (9).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Thus, since our study population consisted primarily of postmenopausal women, it is not surprising that we detected no relationship between IGF-I and breast cancer risk. We also did not find any association between IGF-II and risk of breast cancer, as has been reported previously (7). However, evidence from animal and cell line experiments examining the role of IGF-II in carcinogenesis indicates increased rates of malignancies, including breast tumors (28)(29)(30)(31)(32)(33), and results from one case-control study found a positive association between IGF-II and ER-positive but not ER-negative breast cancer among postmenopausal women (9).…”
Section: Discussionsupporting
confidence: 70%
“…These analyses also took into account potential effects of hyperinsulinemia, by including insulin and leptin, which we show to have no independent associations with breast cancer of their own accord. Serum IGF-I appears to be associated with risk of breast cancer among premenopausal women (7,10,12,13,15,17,24,25), but no similar association has been found among postmenopausal women (10,26). Several explanations for this dichotomy have been proposed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We considered several possible explanations for this difference. First, the complex interactions among Ca, vitamin D and insulin-like growth factors may promote growth inhibition in breast cancer cells (13,49) . Second, Ca may serve as a potential regulator in oestrogen-driven cell proliferation (50) .…”
Section: Discussionmentioning
confidence: 99%
“…De hecho, se ha demostrado que el estradiol acentúa la expresión de la IGF-I y los receptores de ambas hormonas, dando como resultado una interacción sinérgica que estimula la proliferación de células de cáncer de mama (Allen et al, 2005).…”
Section: Insulina: Su Influencia Y Su Papel Como Factor De Crecimientounclassified